Development of Differentiated Learning Methods on Basic Soccer Skills for Tenth Grade Students - Yusuf, Aswin; Kristina, Putri Cicilia; Handayani, Widya (PPSDP International Journal of Education, 2024)
This journal discusses the development of differentiated learning methods on the basic soccer skills of tenth-grade students at SMK SMTI Bandar Lampung. This research was conducted quantitatively using questionnaires and observation instruments. The results showed that differentiated learning can improve student learning outcomes and provide a better learning experience. Additionally, students showed a positive response to the learning of basic soccer skills. Differentiated learning can be a useful method to enhance student learning outcomes in basic soccer skills.